Pemanfaatan Limbah Botol Plastik Dalam Mendukung Budidaya Kerang Hijau - Susanti Sundari; Putri Endah Suwarni; Burhan Nudin; Andri Oktivendra; Hinfa Mosshananza; Yuli Evadianti (MENARA RIAU, 2022)
Green mussel fishermen in Umbul Asem village use waste plastic bottles as floats for green mussel cultivation using the longline method. Due to the need for these used bottles in large quantities, fishermen usually buy them for IDR 6,000/kg from the community. Form a service team consisting of lecturers, students, Matala, and UTB campus cleaners to collect used plastic bottles from the campus environment to be given to partners to reduce partner expenses in production costs to increase business profits as a benefit of this activity while also reducing waste. The service method used is participatory fishing village community development, a continuation of the previous program there. This activity went well according to the target, and the partners felt it helped. And activities to reduce waste and care for the environment and society will be continued by creating waste banks in the campus environment.